Online learning: anywhere anytime education for specialist nursing. - Bromley, Patricia (Neonatal, Paediatric & Child Health Nursing, 2010)
Contemporary nurses are required to be professionally accountable, to update knowledge, education and skills, and deliver care that is evidence-based and best practice. However, the pressure of combining shift work with family life often excludes continuing education. For nurses to embrace lifelong learning, education needs to be accessible, affordable and flexible. To accommodate this, new methods and models of education are developing with broader use of available resources, including greater access to academic programmes through online learning. The integration of educational technology into nursing education involves a paradigm change in traditional views of learning. Evaluation of contemporary literature into online learning suggests that learning outcomes can be as good as, or even better than, traditional didactic learning models. This paper will explore the issues around online learning, discussing the potential advantages and disadvantages for contemporary postgraduate nurse education. It concludes that the difficulties associated with online learning can be minimised with quick and easy access to electronic learning resources and technical support and adequate facilitation both online and in the clinical area.